Millet crop-loss assessment methods - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1994)
Losses of the millet crop in the Sahel are seldom adequately monitored, yet an assessment of such losses is essential in evaluating the effects of, and need for, different farming inputs and methods. This bulletin has been compiled in collaboration...